Simultaneous ACL–PCL reconstructions with high tibial osteotomy: salvage for an unstable arthritic knee. (13th January 2016) - Beyzadeoglu, Tahsin; Demirel, Murat; Circi, Esra
Abstract : We present a case of a 28-year-old man with a severe osteoarthritic varus knee after a neglected multiligamentous injury sustained 10 years prior. Simultaneous anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) reconstructions with high tibial osteotomy (HTO) were performed at a single stage. Five years after surgery, there were no signs of effusion and no instability, and the patient could easily kneel down without any discomfort. We think that salvage procedures and biological reconstructions would be the primary choice of surgical treatment in young patients to delay arthroplasty, and it is possible to perform simultaneous reconstructions of ACL and PCL with HTO in a single stage.